การส่งเสริมการจัดการโลจิสติกส์และโซ่อุปทาน: กรณีศึกษา ผลิตภัณฑ์โอทอป จังหวัดสมุทรปราการ - จารุธีรศานต์ ปิยะฉัตร; ศรีทอง จรีพร (Ph.D. in Social Sciences Journal, 2017)
การส่งเสริมการจัดการโลจิสติกส์และโซ่อุปทาน กรณีศึกษาผลิตภัณฑ์โอทอป จังหวัดสมุทรปราการ มีวัตถุประสงค์เพื่อทราบสภาพทั่วไป ปัญหาและอุปสรรคของการจัดการโลจิสติกส์และโซ่อุปทาน ตลอดจนค้นหาปัจจัยที่มีผลต่อการจัดการโลจิสติกส์และโซ่อุปทานของกลุ่มผลิตภัณฑ์สินค้าโอทอปในจังหวัดสมุทรปราการเพื่อนำเสนอแนวทางการดำเนินงานด้านการจัดการโลจิสติกส์และโซ่อุปทานให้มีประสิทธิภาพยิ่งขึ้น ผู้วิจัยเก็บข้อมูลจากผู้ประกอบการโอทอปด้วยแบบสอบถามจำนวน 400 ชุด ผลการวิจัยพบว่า ปัจจุบันผู้ประกอบการโอทอปดำเนินกิจกรรมโลจิสติกส์ในภาพรวมอยู่ในระดับปานกลางและให้ความสำคัญต่อกิจกรรมโลจิสติกส์ ในภาพรวมอยู่ในระดับมาก ผู้ประกอบการมีความรู้เกี่ยวกับการจัดการ โลจิสติกส์อยู่ในระดับน้อย มีการดำเนินกิจกรรมโซ่อุปทาน ในภาพรวมอยู่ในระดับมาก และให้ความสำคัญต่อกิจกรรมโซ่อุปทาน ในภาพรวมอยู่ในระดับมาก ผู้ประกอบการมีความรู้เกี่ยวกับการจัดการโซ่อุปทานอยู่ในระดับน้อย ผลการทดสอบสมมติฐาน โดยใช้สถิติการวิเคราะห์ความแปรปรวน (Analysis of Variance-ANOVA) ที่ระดับความเชื่อมั่น 0.05 พบว่า ระดับการศึกษา ตำแหน่งงานในธุรกิจและระยะเวลาการดำเนินธุรกิจ ไม่มีผลต่อการจัดการโลจิสติกส์และโซ่อุปทานที่มีประสิทธิภาพของกลุ่มผลิตภัณฑ์โอทอป จังหวัดสมุทรปราการ ความรู้เกี่ยวกับการจัดการโลจิสติกส์และโซ่อุปทานมีผลต่อการจัดการโลจิสติกส์และโซ่อุปทานที่มีประสิทธิภาพของกลุ่มผลิตภัณฑ์โอทอป จังหวัดสมุทรปราการ PROMOTING THE LOGISTICS AND SUPPLY CHAIN: A CASE STUDY OF OTOP PRODUCTS, SAMUT PRAKARN PROVINCE The study entitled promoting the logistics and supply chain: a case study of OTOP products Samut Prakarn province aims to investigate the general condition, problems and barriers of management of logistics and supply chain as well as factors affecting the management of logistics and supply chain of OTOP products in Samut Prakan province. Based on the investigation data, guidelines on the management of logistics and supply chain for higher efficiency was proposed. The data were collected from the OTOP entrepreneurs using questionnaires with 400 returned results. The results showed that the entrepreneurs currently have been doing logistics activities in overall at the average level. The overall level was high for that entrepreneurs gave priority of logistics activities. The overall level of entrepreneurs knowledgeable about managing logistics was at a low level. The entrepreneurs currently had supply chain activities at a high level as well as the importance of supply chain activities. The entrepreneurs had knowledge of supply chain management at a low level. The hypothesis testing by using statistical analysis of variance (ANOVA) at the confidence level of 0.05 could conclude that the common factors of OTOP entrepreneurs, including education, jobs in business and period of business operation did not affect the efficient management of logistics and supply chain of OTOP products, Samut Prakarn province. Knowledge about logistics and supply chain management affects to effective logistics and supply chain management of OTOP products group, Samut Prakarn province.